Antimicrobial Activity of Copper Alone and in Combination with Lactic Acid against Escherichia coli O157:H7 in Laboratory Medium and on the Surface of Lettuce and Tomatoes. (28th August 2011) - Gyawali, Rabin; Ibrahim, Salam A.; Abu Hasfa, Salma H.; Smqadri, Shahnaz Q.; Haik, Yosef
Abstract : The objective of this study was to evaluate the effect of copper alone and in combination with lactic acid against E. coli O157:H7 in laboratory medium and on the surface of lettuce and tomatoes. Four strains of E. coli O157:H7 were individually inoculated into BHI broth containing different concentrations of copper (5, 10, 20, and 40 ppm, w/v), lactic acid (0.1 and 0.2%, v/v), and their combinations. After incubation, aliquots of 1 mL from each sample were withdrawn and plated on BHI agar to determine the bacterial population. Significant growth inhibition (P < 0.05 ) was observed with a combination treatment of copper (40 ppm) and lactic acid (0.2%). The population of E. coli O157:H7 was reduced by 3.93 and 3.39 log on the surface of lettuce and tomato samples, respectively, when treated with the same combination. This indicates that combination of copper and lactic acid could be used as an effective solution to inhibit E. coli O157:H7 on fresh produce.